DEVELOPING ACADEMIC WRITING SKILLS IN FOREIGN LANGUAGE COURSES - Elvira E. Valeeva (Высшее образование в России)
Abstract. The paper presents the experience in forming academic writing skills within the minor program “Business English Translator” at Kazan National Research Technological University. The author considers the training elements of academic writing skills, such as grammar, morphology, and stylistics, as well as their practical application for preparing and publishing scientific papers in foreign journals.